EFFECTIVENESS OF USING THE FLIPPED CLASSROOM STRATEGY IN LEARNING BASIC MOVEMENTS OF FREESTYLE SWIMMING AMONG PHYSICAL EDUCATION FEMALE STUDENTS AT BIRZEIT UNIVERSITY - HAMMAD, REEM; MADDEH, TALEL; ABDELLAOUI, SABER; ABDERRAHMAN, ABDERRAOUF BEN (TPM – Testing, Psychometrics, Methodology in Applied Psychology, 2025)
This study examined the effectiveness of the flipped classroom strategy in teaching the basic movements of freestyle swimming among female students of physical education at Birzeit University. A purposive sample of (40) students enrolled in the "Swimming (2)" course during the summer semester (2023–2024) was selected. Participants were divided into two equal groups: an experimental group that received instruction through the flipped classroom approach and a control group that followed a traditional program. The experimental method was applied with pre-tests and post-tests conducted for physical and skill-related variables. Data were analyzed using SPSS. The results indicated statistically significant improvements at the level of (α ≤ 0.05) in all physical and skill performance variables of freestyle swimming among the experimental group, favoring the post-test. In the control group, significant differences were also found in some physical variables such as standing vertical jump, trunk rotation, and sit-up performance, as well as in basic swimming skills, also in favor of the post-test. However, no significant differences were observed in the medicine ball throw test for the control group. When comparing post-test results between the two groups, the experimental group demonstrated significantly higher improvements across all physical and swimming skill variables than the control group. The findings highlight the positive impact of the flipped classroom strategy on enhancing physical abilities and skill acquisition in swimming. It is recommended to expand its application to other sports and scientific courses in physical education programs.